(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Seven mutants along with the mother variety were evaluated following randomized complete block design with four replicates at four rapeseed growing areas of Bangladesh during 2013-2014 to observe their performances regarding seed yield and yield attributes, and to select promising mutants having higher seed yield with short maturity period. Analysis of variance showed highly significant variations among the mutants and the check for most of the characters studied in individual location and combined over locations. The mutant RM-01-07 required the shortest maturity period except Rangpur and the mother variety Binasarisha-4 required the longest. At Mymensingh and Rangpur, mutant RM-02-07 produced the tallest plant. Both at Mymensingh and Magura, RM-01-07 produced the highest number of siliquae plant-1 and the mother variety produced the lowest siliquae plant-1. At Ishurdi, RM-10-07 produced the highest number siliquae followed by RM-03-07. Combined means over locations showed that the six mutants matured earlier except the mutant RM-03-07 and most of the mutants produced higher number of branches plant-1 compared to the mother variety. Results over different locations also showed that the three mutants RM-01-07, RM- 10-07 and RM-04-07 produced significantly higher seed yield (1912, 1846 and 1862 kg/ha, respectively) which was 15.1, 12.1 and 11.1% higher than the mother variety, Binasarisha-4 with seed yield of 1661 kg/ha. These three mutants had also the higher number of siliquae than the mother variety. This suggests that gamma rays irradiation can be fruitfully applied to develop mutants with higher seed yield and other improved agronomic traits in oleiferous Brassica. J. Bangladesh Agril. Univ. 14(2): 141-146, December 2016